2014
DOI: 10.1002/2013jd021168
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of winter climate transitions to snow and clouds over the Prairies

Abstract: Using data from 13 climate stations on the Canadian Prairies, together with opaque cloud cover and daily snow depth, to analyze the winter climate transitions with snow, we find that a snow cover acts as a fast climate switch. Surface temperature falls by about 10 K with fresh snowfall and rises by a similar amount with snowmelt, while the daily range of relative humidity falls to around 5-15% with snow cover. These are robust climate signals. For every 10% decrease in days with snow cover over the Canadian Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 54 publications
7
112
0
Order By: Relevance
“…This was pointed out by Wang and Zeng (2014), who showed that if DTR is determined from the monthly mean diurnal cycle, found by averaging the hourly data for a month, the coupling between DTR and the diurnal radiative forcing emerges, even at high latitudes and in winter. Betts et al (2014a) briefly explored this for these Prairie data, and found similar results in winter as well as significant differences in summer. The reason is that when it is cloudy or the surface is snow covered, the diurnal range of temperature driven by the diurnal radiative forcing (SWCF and LWCF) is small compared to typical daily advective changes.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…This was pointed out by Wang and Zeng (2014), who showed that if DTR is determined from the monthly mean diurnal cycle, found by averaging the hourly data for a month, the coupling between DTR and the diurnal radiative forcing emerges, even at high latitudes and in winter. Betts et al (2014a) briefly explored this for these Prairie data, and found similar results in winter as well as significant differences in summer. The reason is that when it is cloudy or the surface is snow covered, the diurnal range of temperature driven by the diurnal radiative forcing (SWCF and LWCF) is small compared to typical daily advective changes.…”
Section: Introductionmentioning
confidence: 82%
“…Betts et al (2014a) showed that in winter, and even in summer under cloudy conditions, that stratification by opaque cloud shows substantial differences between DTR and DRH calculated by averaging daily ranges, and values found from the mean diurnal cycles derived by averaging the hourly data. We explored this (Section Radiatively Forced Diurnal Ranges and Mean Diurnal Ranges) and concluded that for conceptual purposes the "true" diurnal cycle, meaning that which is coupled to the diurnally varying radiation field, is found by first compositing the hourly data for groups of many days, and then determining the diurnal ranges from the composites.…”
Section: Diurnal Range Choicesmentioning
confidence: 91%
See 3 more Smart Citations